A Rare Encounter: Incidental Ectopic Origin of the Right Pulmonary Artery in an Adult - Jain, Rupali; Kumaran, Maruti; Donuru, Achala (AORTA, 2024)
Ectopic origin of the right pulmonary artery (RPA) from the aorta is a rare congenital anomaly typically found in infants. We report an adult female presenting with shortness of breath diagnosed incidentally with ectopic RPA via computed tomography angiography. This case underscores the need to consider rare congenital anomalies in adults presenting with unexplained pulmonary symptoms.
Keywords: ectopic right pulmonary artery; computed tomography angiography; adult presentation